The effects of individual differences in field dependence/independence and analogical reasoning for L2 instruction. (November 2020) - Meguro, Yoichi
Abstract: The present study, which employed a pre- to posttest design, investigated the impact of second language (L2) learners' individual differences (IDs) in field dependence/independence (FD/FI), analogical reasoning for L2 classroom instruction. The FD/FI style refers to IDs in the degree to which an individual's perception is affected by surrounding information, and analogical reasoning is the ability to discern meaningful patterns across multiple forms of relations. Forty-six Japanese senior high school students participated in the study. They received an explicit rule presentation on English relative adverbs ( where, when, and why ) via textual enhancement. Learner differences in FD/FI and analogical reasoning were measured by the modified Group Embedded Figures Test and the nonverbal analogies test, respectively. The effectiveness of L2 instruction was assessed by the fill-in-the-gap tasks. Results showed (a) that the L2 learning outcomes marginally correlated with analogical reasoning, but not with the FD/FI style; (b) that the analogical reasoning marginally correlated with the combined gain scores of where and when ; and (c) that the learning outcomes seemed to be predicted by the combination of IDs variables (i.e. more FI with higher analogies led to increased L2 learning).